Peran Zakat dan Wakaf Terhadap Kebijakan Fiskal Dalam Perspektif Ekonomi Makro Islam - Nazwa Akhiela Salsabila Batubara; Khoirani Nasution; Ardiansyah Dalimunthe; Ahmad Wahyudi Zein, M.E.I (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Zakat and waqf are unique fiscal instruments in the Islamic economic system that hold significant potential for supporting state fiscal policy. From an Islamic macroeconomic perspective, fiscal policy is directed not only at maintaining economic stability and growth but also at realizing distributive justice and social welfare (falah). This study aims to analyze the role of zakat and waqf in fiscal policy and their implications for Islamic macroeconomic stability, particularly in the context of sustainable development. The research applies a qualitative descriptive framework grounded in a literature review, through a review of Islamic economics literature, scientific journals, and regulations related to zakat and waqf management. The results of the study indicate that zakat functions as an instrument for income redistribution and a fiscal stabilizer capable of reducing social inequality, while waqf serves as a source of long-term financing for the education, health, and public service sectors. The integration of zakat and waqf into Islamic fiscal policy has the potential to strengthen fiscal resilience, increase the efficiency of state spending, and encourage equitable, inclusive, and sustainable economic development.